The Influence of Structural Configuration on Charge Accumulation, Transport, Recombination, and Hysteresis in Perovskite Solar Cells. Issue 3 (30th September 2016) - Wang, Yi; Wang, Hao‐Yi; Han, Jun; Yu, Man; Hao, Ming‐Yang; Qin, Yujun; Fu, Li‐Min; Zhang, Jian‐Ping; Ai, Xi‐Cheng
Abstract: Behind the outstanding photovoltaic performance of perovskite solar cells (PSCs), the correlation between the structural configuration of the PSCs and the mechanism of photoelectric conversion is still not fully understood. In this paper, two types of PSCs with different structural configurations, that is, mesoporous (meso) and planar, were prepared, and systematic optoelectronic transient studies were performed on these devices. Although the photovoltaic performances of the tested meso‐ and planar‐PSCs were comparable, the different structural configurations resulted in distinct charge dynamics and photoelectric conversion mechanisms. By taking the dynamic results into account, the influence of a meso‐TiO2 layer on charge accumulation, transport, and recombination was elucidated. More importantly, an excessively slow temporal response component in the optoelectronic transients was observed, which was proven to be linked to specific hysteresis phenomena in the PSCs. The experimental results collectively indicated that the hysteresis, which showed strong dependence on device structure and charge dynamics, was irrelevant to charge trapping or ferroelectricity but probably resulted from interfacial charge accumulation and/or ion migration. This work provides deep insight into the structure–function relationship in PSCs and highlights the effect of hysteresis on charge dynamics. Abstract : Two kinds of perovskite solar cells (PSCs) with different structural configurations, that is, mesoporous and planar ones, are prepared, and systematic optoelectronic transient studies are performed on these devices. The mesoporous TiO2 film in the meso‐PSC is found to promote charge separation, suppress charge transport/recombination, and alleviate hysteresis. HTM=hole‐transporting material, FTO=fluorine‐doped tin oxide.